Aging damage characteristics of acid‐etched sandstone samples - Aohan Zhao; Yankun Ma; Tong Zhang; Xi Zhang (Energy Science & Engineering)
Abstract To investigate the erosive damage effect of the acidic solution on sandstone, experiments were conducted to examine the macro‐ and micro‐characteristics of sandstone samples under different acid etching times. Microscopic morphology changes, pore structure characteristics, mineral composition changes, and mechanical response characteristics were obtained before and after acid etching. Finally, a comprehensive evaluation index for acid etching damage was proposed. The results show that: (1) Acidic solution will erode the sandstone skeleton and cause the sandstone to collapse. The etched surface appears “flocculent” and yellow sediment is produced. (2) The pores in sandstone samples are mainly micro‐ and mesopores, and the total porosity increases exponentially with the duration of acid etching. The volume fraction of micropores can reach up to 81.5%. (3) The acid etching process of sandstone samples includes physical diffusion and chemical dissolution, which can be divided into four stages and three regions from the outside to the inside. After acid etching, the uniaxial compression failure mode of the sample changes from shear to mixed shear‐tensile failure. (4) The comprehensive evaluation index based on three failure modes generated during the loading process shows good consistency with the overall changes of characteristics parameters such as elastic modulus, peak stress, and peak strain. The research findings of this paper can provide theoretical support for the assessment of rock mass stability and disaster prevention in acidic environments.